The impact of dietary metabolizable energy levels on the performance of medium-sized geese: A systematic review - Shuo Wang; Chunbo Wei; Jiaxin Yan; Ying Zhang (Poultry Science)
This study aimed to investigate the effects of dietary metabolizable energy levels on various performance indicators of medium-sized geese, with the goal of predicting the optimal range of these energy levels. A comprehensive literature search was conducted across several databases, including Chinese National Knowledge Infrastructure, Wanfang, China Science and Technology Journal Database, PubMed, Web of Science, and ScienceDirect, covering the period from January 1, 2000, to July 1, 2024. The gathered studies focused on the impact of dietary metabolizable energy levels on the production performance of medium-sized geese. Following the literature review, a network meta-analysis was conducted by Stata software (StataCorp version 14.0). The analysis included tests for inconsistencies in the results by inconsistency model, assessment of publication bias by funnel plots, and data sorting through the robust error meta-regression model. Additionally, nonlinear dose-response curves were plotted by the restricted cubic spline method to explore the relationships between metabolizable energy levels and production performance indicators. Out of 2267 identified studies, 25 met the inclusion criteria and were incorporated into the systematic review, representing a total sample of 3538 geese. The production performance indicators examined included average daily gain, average daily feed intake, feed-to-gain ratio, and abdominal fat percentage. The results of the network meta-analysis revealed that both direct and indirect comparisons could be made across different dietary metabolizable energy levels reported in the studies. It was observed that increasing dietary metabolizable energy levels significantly impacted certain performance indicators of medium-sized geese. The findings were robust and reliable for further analysis. The dose-response meta-analysis indicated optimal dietary metabolizable energy levels within the existing ranges, specifically 13 to 13.5 MJ/kg for medium-sized geese during the brooding stage, and 12 to 13 MJ/kg during the growing stage. Future research should explore the effects of dietary metabolizable energy levels in large-sized geese, small-sized geese, and diets with higher energy levels to broaden the understanding of energy optimization across different goose sizes and developmental stages.